Pengaruh Kendali Glukosa terhadap Kadar Kalsium Serum pada Penderita DM Tipe 2 di Malang Raya - Ananda Kumala Ansar; Dewi Martha Indria; Rahma Triliana (Jurnal Kedokteran Komunitas (Journal of Community Medicine), 2020)
Introduction : Diabetes mellitus (DM) is a glucose metabolism disorder that is able to cause organ damage if the patient has inadequate glycemic control. Organ damage in patient with DM leads to micronutrient metabolism disorder includes calcium. Decreased serum calcium level in DM patient could reduce the insulin sensitivity. The effect of glycemic control in type 2 DM on calcium serum level in Indonesia has never been studied. Therefore, further research is needed, especially in Malang City.Method : : A cross sectional study with control group post-test-only design was conducted using purposive non-random sampling. Total subject was 40 patients consist of 15 patients with good glycemic control and 25 with poor glycemic control. Each group examined for serum calcium level using Atomic Absorption Spectrophotometry (AAS). Data were analyzed by using Independent T-Test followed by Pearson correlation test with a significance level of p <0.05Results : Calcium level in type 2 DM patients with good glycemic control (4,25±1,54 mg/dL) were higher than poor glycemic control (3,32±1,43 mg/dL) with signifikasi p=0,404. Glycemic control is moderately correlated on serum calcium with correlation level r=-0,358 and signification level p=0,03.Conclusion : Glycemic control in type 2 diabetes mellitus moderate correlated with serum calcium level.Keywords: Glycemic control in type 2 DM is moderately correlated with serum calcium level.